Construction of highly crystalline ultraporous covalent organic frameworks in seconds - Karak, Suvendu; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COFs; Crystalline; Ultraporous

Convergent covalent organic framework thin sheets as flexible supercapacitor electrodes - Khayum, Abdul M.; Vijayakumar, Vidyanand; Karak, Suvendu; Kandambeth, Sharath; Bhadra, Mohitosh; Suresh, Karthika; Acharambath, Nikhil; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Material & Interfaces, 2018)
Flexible supercapacitors in modern electronic equipment require light-weight electrodes, which have a high surface area, precisely integrated redox moieties, and mechanically strong flexible free-standing nature. However, the incorporation of the aforementioned properties into a single electrode remains a great task. Herein, we could overcome these challenges by a facile and scalable synthesis of the convergent covalent organic framework (COF) free-standing flexible thin sheets through solid-state molecular baking strategy. Here, redox-active anthraquinone (Dq) and pi-electron-rich anthracene (Da) are judiciously selected as two different linkers in a beta-ketoenamine-linked two-dimensional (2D) COF. As a result of precisely integrated anthraquinone moieties, COF thin sheet exhibits redox activity. Meanwhile, pi-electron-rich anthracene linker assists to improve the mechanical property of the free-standing thin sheet through the enhancement of noncovalent interaction between crystallites. This binder-free strategy offers the togetherness of crystallinity and flexibility in 2D COF thin sheets. Also, the synthesized porous crystalline convergent COF thin sheets are benefited with crack-free uniform surface and light-weight nature. Further, to demonstrate the practical utility of the material as an electrode in energy-storage systems, we fabricated a solid-state symmetrical flexible COF supercapacitor device using a GRAFOIL peeled carbon tape as the current collector.

Connecting microscopic structures, mesoscale assemblies, and macroscopic architectures in 3D-printed hierarchical porous covalent organic framework foams - Mohammed, Abdul Khayum; Usgaonkar, Saurabh; Kanheerampockil, Fayis; Karak, Suvendu; Halder, Arjun; Tharkar, Minakshi; Addicoat, Matthew; Ajithkumar, Thalasseril G.; Banerjee, Rahul (Journal of the American Chemical Society, 2020)
The induction of macro and mesopores into two-dimensional porous covalent organic frameworks (COFs) could enhance the exposure of the intrinsic micropores toward the pollutant environment, thereby, improving the performance. However, the challenge is to build a continuous hierarchically porous macro-architecture of crystalline organic materials in the bulk scale. In this regard, we have strategized a novel synthetic method to create hierarchically porous COF foams consisting of ordered micropores (2-2.2 nm) and disordered meso and macropores (50 nm to 200 mu m) as well as ordered macropores (1.5 mm to 2 cm). Herein, graphene oxide was used for creating disordered macro and mesopores in COF-GO foams. Considering the rheological features of the precursor hydrogel, we could integrate crystalline and porous COF-GO foams into self-supported three-dimensional (3D)-printed objects with the desired shapes and sizes. Therefore, we have engineered the 3D macro-architecture of COF-GO foams into complex geometries keeping their structural order and continuous porosity intact over a range of more than a million (10(-9) m to 10(-3) m). The interconnected 3D openings in these COF-GO foams further enhance the rapid and efficient uptake of organic and inorganic pollutants from water (>95% removal within 30 s). The abundant distribution of interconnected macroporous volume (55%) throughout the COF-GO foam matrix enhances the flow of water (1.13 x 10(-3) m.s(-1)) which results in efficient mass transport and adsorption.